Psoriasis and cardiometabolic disorders - Julia Nowowiejska; Anna Baran; Iwona Flisiak (Termedia Publishing House, 2021)
Psoriasis is a chronic, inflammatory, autoimmune skin disease affecting 2-4% of general population. It is an important social issue, because of its confirmed associations with metabolic syndrome. Individals with psoriasis are at an increased risk of developing cardiovascular disorders and diabetes mellitus. Psoriasis and its comorbidities have multiple common pathogenic pathways including the chronic inflammatory process, immunological abnormalities, genetic links and different bioactive proteins secreted by the adipose tissue. Considering the above associations, it is advisable to perform screening tests in patients with psoriasis to detect metabolic disorders as they not only increase mortality in these individuals, but also decrease their life quality significantly. An essential issue is also the education and the improvement of doctor-patient relationship, as well as early introducing of preventive measures.